ANALISIS USAHATANI PADI SAWAH DI DESA KEMUNING MUDA KECAMATAN BUNGARAYA KABUPATEN SIAK - Sopan Sujeri; Evy Maharani; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Subsystem primary produce is activity of related to use medium and produce paddy. The purpose of this study to analyze farming primary produce of paddy in Kemuning Muda village, with consideration Kemuning Muda village owning wide of farm and the highest of paddy production. This study of during executed three months. Started on December 2014 until April 2015. The analysis used farming analysis R/C and B/C ratio, and descriptive analysis. The result of research showed that average of production total cost every Ha is Rp.9.848.279,51. The average gross income of farming paddy every Ha is Rp.20.059.134,64, while the average net income every Ha is Rp.10.210.605,13. Based on the result of research R/C and B/C ratio on the basis of the average total cost, value of R/C and B/C ratio is 1,08. It means every expenditure of Rp.100,00 will generate Rp.108,00. The value R/C and B/C ratio on the basis of variable cost is 1,61. It showed every expenditure of Rp.100,00 will generate Rp.1,61. The value R/C and B/C ratio showed on the basis average total cost and average variable cost to farming in Kemuning Muda village that are profit and profitable. Keywords: Farming, paddy, net income, efficiency.